Pengaruh Disiplin Kerja dan Motivasi Kerja terhadap Kinerja Karyawan dengan Kepuasan Kerja sebagai Variabel Intervening pada Rumah Sakit Sri Pamela Tebing Tinggi - Rusmewahni Rusmewahni; Willy Cahyadi; Rizki suci Ramadhani (Departement of Mathematics Education, 2023)
This study aims to determine how the effect of work discipline and work motivation on employee performance with job satisfaction as an intervening variable at Sri Pamela Cliff High Hospital. The population in this study were 60 non-medical employees at Sri Pamela Tebing Tinggi Hospital. Samples were taken as many as 60 respondents using saturated sampling techniques because the number of samples was below 100. The regression analysis method used was multiple linear regression and to test the hypothesis used the t test and path analysis test. The research data were analyzed or processed using the SPSS version 25 program. From the results of this study it can be concluded that work discipline has an effect on job satisfaction of employees, work motivation has an effect on leadership style on employees, job satisfaction has an effect on job satisfaction on employees, work discipline has an effect on employee performance on employees, work motivation has no effect on employee performance on employees, job satisfaction has an effect on employee performance, job satisfaction is not a mediating variable between work discipline on employee performance, job satisfaction is a mediating variable between motivation on employee performance.